Library Benchmarking - Suwarno, Wiji (Pustakaloka, 2010)
The term benchmarking has been encountered in the implementation of total quality (TQM) or in Indonesian termed holistic quality management because benchmarking is a tool to look for ideas or learn from the library. Benchmarking is a processof measuring and comparing for continuous business process of systematic and continuous measurement, the process of measuring and comparing for continuous business process of an organization to get information that can help these organization improve their performance efforts.